Program Peningkatan Kompetensi SDM Untuk Mendukung Transformasi Ekonomi Lokal - Priya Sevilyani; Isti Anjeli Apriliani; Amelda Putri Febriyanti; Jaisy Marisa Anugrah J; Nurwahidah Oktavia (CV. Multi Kreasi Media, 2024)
The human resource (HR) competency improvement program is a strategic step to support local economic transformation, especially in Cicalengka Village, Pagedangan Subdistrict. This program is designed to address the main challenges faced by village communities, such as low work skills, limited access to training, and lack of innovative business opportunities. The main focus of this program is on developing local potential-based skills, such as entrepreneurship training, agricultural product management, and mastery of digital technology. Through a participatory approach, this program involves the village government, local business actors, and community organizations in designing and implementing training activities that are relevant to community needs. In addition, technology support and marketing networks are strengthened to open access to a wider market. The results of this program are expected to increase community productivity and income, create new jobs, and strengthen local economic resilience. Thus, economic transformation in Cicalengka Village can run in an inclusive, sustainable, and community empowerment-based manner.